Convergence of Solutions of Certain Fourth-Order Nonlinear Differential Equations - Ogundare, B. S.; Okecha, G. E. (2014)
We give sufficient criteria for the existence of convergence of solutions for a certain class of fourth-order nonlinear differential equations using Lyapunov's second method. A complete Lyapunov function is employed in this work which makes the results to include and improve some existing results in literature.